Iraq then and now - King, John, 1939- (Chicago, Ill. : Raintree, 2006)
Provides a history of Iraq and describes its relationship with the West, particularly focusing on the government, politics, and foreign relations of the country after Saddam Hussein became president in 1979.
"We got him!" -- The first civilizations -- Islam comes to Iraq -- Mongols, Kurds, and Turks -- 1921: Britain creates the Kingdom of Iraq -- The monarchy: 1921-1958 -- Military regimes: 1958-1968 -- The Baath in power: 1968-1979 -- Saddam as president -- War with Iran -- 1990: The invasion of Kuwait -- 1991: Iraq driven out of Kuwait -- 1991-2001: Sanctions and the effects -- 1991-2002: The no-fly zones -- 1991-2001: Sanctions: the inspections -- September 11: A turning point -- Iraq and the United Nations -- The invasion of Iraq -- Sunnis, Kurds, and Shi'ites -- 2003-2004: Resistance continues -- Interim government -- Turbulent Iraq.
Includes bibliographical references (page 54) and index.
Keywords: Iraq -- History -- 1921- -- Juvenile literature